Cytotoxic T cells induce proliferation of chronic myeloid leukemia stem cells by secreting interferon-γ - Schürch, Christian (The Rockefeller University Press, 2013)
Chronic myeloid leukemia (CML) is a clonal myeloproliferative neoplasia arising from the oncogenic break point cluster region/Abelson murine leukemia viral oncogene homolog 1 translocation in hematopoietic stem cells (HSCs), resulting in a leukemia stem cell (LSC). Curing CML depends on the eradication of LSCs. Unfortunately, LSCs are resistant to current treatment strategies. The host’s immune system is thought to contribute to disease control, and several immunotherapy strategies are under investigation. However, the interaction of the immune system with LSCs is poorly defined. In the present study, we use a murine CML model to show that LSCs express major histocompatibility complex (MHC) and co-stimulatory molecules and are recognized and killed by leukemia-specific CD8(+) effector CTLs in vitro. In contrast, therapeutic infusions of effector CTLs into CML mice in vivo failed to eradicate LSCs but, paradoxically, increased LSC numbers. LSC proliferation and differentiation was induced by CTL-secreted IFN-γ. Effector CTLs were only able to eliminate LSCs in a situation with minimal leukemia load where CTL-secreted IFN-γ levels were low. In addition, IFN-γ increased proliferation and colony formation of CD34(+) stem/progenitor cells from CML patients in vitro. Our study reveals a novel mechanism by which the immune system contributes to leukemia progression and may be important to improve T cell–based immunotherapy against leukemia.